Trauma to the neck: Manifestation of injuries outside the original zone of injury-A case report - Christakis, Alexander; Tashjian, Brian; Gilroy, Anne M; Heard, Stephen O (Archives of Case Reports, 2018)
A 53-year-old male presented to the Emergency Department (ED) with multisystem trauma and respiratory distress following a blunt-force injury to his anterior left neck. CT imaging showed extensive subcutaneous emphysema and pneumomediastinum. A chest X-ray showed elevation of the left hemidiaphragm suggesting phrenic nerve injury which was confirmed by bedside ultrasonographic examination of the left hemidiaphragm. Flexible bronchoscopy demonstrated tracheal rupture. The patient was treated supportively and recovered without surgical treatment. Trauma-induced hemidiaphragmatic paralysis is rarely reported. This case represents a clinical scenario with demonstrable anatomic correlations, and a clinical reminder that phrenic nerve injury should be included in the differential diagnosis of respiratory distress in a trauma patient.